Proanthocyanidins-loaded complex coacervates-based drug delivery attenuates oral squamous cell carcinoma cells metastatic potential through down-regulating the Akt signaling pathway - Liu, Ju-Fang; Wee, Yinshen; Luo, Shen-Dean; Chang, Shwu-Fen; Jia, Shihai; Feng, Sheng-Wei; Huang, Huei-Mei; Lin, Jiann-Her; Wang, Ching-Shuen (Frontiers in Oncology, 2022)
Oral cancer, constituted up to 90% by squamous cell carcinomas, is a significant health burden globally. Grape seed proanthocyanidins (PA) have been suggested as a potential chemopreventive agent for oral cancer. However, their efficacy can be restricted due to the low bioavailability and bioaccessibility. Inspired by sandcastle worm adhesive, we adapted the concept of complex coacervation to generate a new type of drug delivery platform. Complex coacervates are a dense liquid phase formed by the associative separation of a mixture of oppositely charged polyelectrolytes, can serve as a drug delivery platform to protect labile cargo. In this study, we developed a complex coacervates-based delivery of PA. The release kinetics was measured, and anticancer effects were determined in two human tongue squamous cell carcinoma cell lines. The results showed that complex coacervate successfully formed and able to encapsulate PA. Additionally, PA were steadily released from the system in a pH-dependent manner. The drug delivery system could significantly inhibit the cell proliferation, migration, and invasion of cancer cells. Moreover, it could markedly reduce the expression of certain matrix metalloproteinases (MMP-2, 9, and 13) crucial to metastatic processes. We also found that suppression of protein kinase B (Akt) pathway might be the underlying mechanism for these anticancer activities. Taken together, complex coacervates-based delivery of PA can act as an effective anticancer approach for oral cancer therapy.